Proliferation and apoptosis in early molar morphogenesis-- voles as models in odontogenesis - Setkova, Jana; Lesot, Herve; Matalova, Eva; Witter, Kirsti; Matulova, Petra; Misek, Ivan (The International journal of developmental biology, 2006)
Proliferation and apoptosis play crucial roles in the development of multicellular organisms. Their precise balance is necessary for tissue homeostasis throughout life. The developing dentition is a suitable model to study proliferation and apoptosis during embryogenesis, but the corresponding studies have been carried out principally in the mouse. The present study aimed to examine proliferation and apoptosis in the vole (Microtus sp., Rodentia) during the early morphogenesis of the first upper molar and compare it to what is known from the mouse. To this end, apoptosis and proliferation were investigated using histology and computer-aided 3D reconstruction. Mitoses accumulated predominantly in the developing cervical loop. Apoptosis during early odontogenesis showed highly specific spatio-temporal patterns in the dental epithelium. Apoptotic bodies were localised in non-dividing cell populations. They accumulated in the same places as described in the mouse: antemolar vestiges (ED 12.5 15.5), enamel knot (ED 14.5 15.5), stalk and palatally along the whole first molar tooth germ longitudinal axis (ED 15 - 15.5). Early tooth development in the field vole, including the distribution of apoptosis and mitosis, is very similar to that reported in the mouse, with the exception of the antemolar region. The microtine antemolar vestige is preserved longer than the murine one. It is conceivable that additional distinct differences in morphogenetic processes appear later in tooth development.
Keywords: odontogeneze; Maxilla; Apoptosis; druhová specificita; Odontogenesis; gestační stáří; Models, Biological; mitóza; zvířata; proliferace buněk; myši; počítačové zpracování obrazu; Image Processing, Computer-Assisted; Mice; apoptóza; Arvicolinae; Cell Proliferation; biologické modely; Mitosis; moláry; Species Specificity; Animals; Molar; Gestational Age; maxila